(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This article analyzes a collection of short stories Iz prošlosti [From the Past] by Isidora Sekulić and Rebecca West’s novel The Return of the Soldier, trying to show how they describe the civil society during World War I. As women who are not actively participating in the battles, both authors spend the war in their respective civil societies and examine how different social groups perceive this historical event. In the end, both of them focus on distinguishable characters who grow to become the representatives of the entire generation, thus combining the individual and collective. Isidora Sekulić’s short stories thematize the life of Serbs in Vojvodina and their wartime transition from oppression to liberation, which makes the collection Iz prošlosti an important part of not just her literary engagement, but the entire corpus of the Serbian prose that speaks of this war. On the other hand, Rebecca West’s novel analyzes feminine experience of the war and the everyday life far away from the front, but also introduces the topic of psychological trauma as a consequence of the war and psychoanalysis as a way to deal with that trauma.